Criminal policy against the criminal actions of damning good name through Social Media - Imam Makhali; Arief Darmawan; Otto Yudianto; Erny Herlin Setyorini (Technium Social Sciences Journal, 2021)
This study uses normative research, using several approaches to statutory regulations, philosophical approaches and conceptual approaches. Advances in information technology can simplify and accelerate electronic communication with the potential to have negative impacts, such as the birth of new crimes, including defamation cases through social media, law enforcers can provide different interpretations, and it’s not uncommon for Judges as the last bastion to enforce the law, in implementing the law they don’t really provide justice and consistency of decisions. Electronic Transaction Information Law has not been able to provide a sense of justice in the articles there are multi-interpretation rubber articles that are easily interpreted unilaterally by law enforcement officials. Criminal law policy is an effort to prevent criminalization in providing protection to the community, through criminal law policies for legislators, applicable policies and executive policies.